Geophysical and Hydrochemical Studies to Map Saltwater Infiltration into Freshwater aquifers: A case study of Ikoyi, Lagos State, Nigeria - Airen, O. J.; Babaiwa, D. A. (European Scientific Journal, ESJ, 2022)
A total of three electrical imaging lines were measured using the Wenner configuration. And a total of fifteen VES was carried out within the area of investigation and six water samples was collected. The results were presented as profiles, model sections, inverted sections and tables. Interpretations of these results involve both qualitative and quantitative deductions from 1D and 2D geoelectric models and laboratory analysis for the water analysis. The VES data were processed by partial curve matching to generate the 1st order geoelectric parameters and inverted in 1D using the WinResist. The 2D resistivity data were processed by inversion using the DIPROFWIN to generate the 2D resistivity section across each traverse while the water samples were taken to the laboratory for comprehensive analysis. The 2D resistivity structures reveal the lateral and the vertical subsurface information with resistivity values ranging from 0.130 to 4741 Ωm. The resistivity values are representative of the clay, clay (saline), clayey sand (saline), clayey sand and sand. From the quantitative interpretation five to six distinct layers were identified. The layers are: topsoil, clayey sand, clay, saline clayey sand, saline clay and sand. The resistivity of the topsoil varies from 38.2 Ωm to 155.3 Ohm-m. The resistivity of the sand varies from 100.8 Ωm to 115.8 Ωm. The resistivity of clayey sand varies from 56.6 Ωm to 90.1 Ωm. The resistivity of clay varies from 12.7 Ωm to 41.2 Ωm. The resistivity of the saline layer (saline clayey sand/clay) varies from 2.1 Ωm to 51.2 Ωm. The depth of saline clay interface varies from 25.7 m to 72.6 m. The depth to the saline clayey sand interface varies from 25.7 - 72.6 m. The chemical analysis of water samples showed that the pH varies from 7.05 to 8.42, total dissolved solids vary from 1786 to 2116 mg/L and electrical conductivity varies from 2106 to 2656 µS/cm. The anions and cation concentrations such as Ca2+, Mg2+, Na+, K+, Cl- and HCO3- ranges from 158 to 185 mg/L, 36 to 48 mg/L, 222 to 287 mg/L, 3.2 to 3.8 mg/L, 10.86 to 20.87 mg/L and 2.33 to 3.88 mg/L respectively. The ratio of Cl/HCO3- ion ranges from 4.05 to 7.67. The interpreted results show saline water intrusion where they occur in different part of the area investigated. The results showed the effectiveness and usefulness of electrical resistivity method in mapping saline water intrusion problem in coastal areas. However, it is necessary to carry out integrated geophysical surveys involving electrical resistivity and induced polarization methods prior to drilling in the study area.